An Overview of Heavy Metal Contamination of Water and Its Effect on Human Health - Danjuma, M.S.; Abdulkadir, B. (UMYU Journal of Microbiology Research)
Heavy metals are naturally occurring elements that have a high atomic weight and a density at least five times greater than that of water. The continuous industrial activities that generate metals have led to their wide distribution in the environment which raised a concern over the effects of such metals on human health and the environment itself. These metals are of great concern as some of them were found to be toxic and persistent even at low concentration. Industrial activities that includes; tannery, textile and other industries use chemicals must of which contains certain amount of heavy metals, discharges their untreated effluents into the nearest water bodies and lead to modification and increase in the background concentration of the metals (including those naturally in the water body). The aim of this review is to assess the contamination of water bodies by heavy metals as a result of industrial discharge of untreated waste into the water and also the health effect related to heavy metals on the human populace. Available information on current publications from scientific journals and other relevant sources were carefully used for this review. Some of the reviewed literatures indicated that must heavy metals are found to be toxic depending on their concentrations and persistent nature. Other factors that affect the toxicity of metals include; their biological role, pH of the medium, and the organisms in question (Human). Upon all the heavy metals present in the environment, Pb, Zn, Cd, Mn, and Co were given more attention in terms of water pollution. Many of these metals undergo methylation as a result of accumulation where bacteria absorb the metals and convert them into a toxic organometallic compounds. As these metals become incorporated with organic components, they tend to be readily available for uptake into the food chain. These heavy metals become toxic in the living system when they are not metabolized by the body and leads to accumulation in the soft tissue. It was observed that this toxic effect can result into damaged or reduced mental and central nervous system function, lower energy levels and damage to blood composition, lungs, kidney, liver, and other vital or essential organs in human beings and other mammals. Prolonged exposure may result in retard progressing physical, muscular, and neurological degenerative processes, allergies and to some extent continuous exposure may lead to cancer. Metal contamination of water pose a serious risk of exposure to both plants and animals including humans. Therefore, continuous use of such contaminated water for both agricultural and domestic purposes may affect the populace either at short or long term.